2019
DOI: 10.1186/s12939-019-0937-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral health on Australian urban Aboriginal and Torres Strait Islander families: a qualitative study

Abstract: Background The oral health of a child not only impacts the physical well-being of the child, but can have quality of life implications for parents and families as they endeavour to provide care and support their child’s oral health needs. Within Australia, Aboriginal and Torres Strait Islander children are thought to experience a disproportionate burden of poor oral heath compared to non-Indigenous children. Despite the prevalence of oral health challenges, there are limited qualitative studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 33 publications
3
58
0
Order By: Relevance
“…In this study, mothers reported feeling guilty, possibly blaming themselves for the problems caused by caries to their children. This reinforces previous qualitative study which showed that child oral health can impact their family's quality of life, contributing to stress, financial challenges, and at times affecting their physical health . It has been shown that cavitated lesions can make parents upset and feeling guilty about the condition of their children .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, mothers reported feeling guilty, possibly blaming themselves for the problems caused by caries to their children. This reinforces previous qualitative study which showed that child oral health can impact their family's quality of life, contributing to stress, financial challenges, and at times affecting their physical health . It has been shown that cavitated lesions can make parents upset and feeling guilty about the condition of their children .…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the few studies 14,15 to conduct a qualitative assessment showing the wide-ranging impacts of dental caries in children and their families. The mothers interviewed in this study reported that the presence of caries on anterior teeth had direct consequences in children's and family's everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…Senior members of the community indicated that oral health ought to be researched as well because there were limited data available on the oral health of urban Indigenous families, and the community was unable to effectively advocate for additional oral health resources. In conjunction with the respiratory study, a quantitative oral health study investigating the prevalence of caries and the associated risk factors was undertaken, and the results published [22][23][24][25]. Additionally, a qualitative study was proposed to provide a voice to the participants and assist in understanding the impact child oral health was having on families.…”
Section: Setting and Contextmentioning
confidence: 99%
“…The study utilised PAR principles and in collaboration with the researcher, two participants took part in coding and theming the data to answer the research question. The results were published [25]. However, in addition to the data relevant to the research question, participants also contributed data which was deemed unrelated (as determined by the participants and researcher) to the initial research question, but valuable to the participants and their narrative.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation